2014
DOI: 10.2527/jas.2013-7193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D status improvement with 25-hydroxycholecalciferol on skeletal muscle growth characteristics and satellite cell activity in broiler chickens1,2

Abstract: Skeletal muscle satellite cells (SC) play a critical role in the hypertrophic growth of postnatal muscle. Increases in breast meat yield have been consistently observed in broiler chickens fed 25-hydroxycholecalciferol (25OHD3), but it is unclear whether this effect is mediated by SC. Thus, our objective was to determine the effect of vitamin D status improvement by replacing the majority of dietary vitamin D3 (D3) with 25OHD3 on SC activity and muscle growth characteristics in the pectoralis major (PM) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 30 publications
2
41
1
Order By: Relevance
“…Overall, plasma 25D 3 levels were significantly increased by higher vitD supplementation and by offering 25D 3 as the source of vitD activity in both uninfected and infected birds. The interaction between level and source indicates that offering 25D 3 is more efficient than D3 in raising its concentration and is consistent with previous reports in chickens where serum or plasma concentrations of the metabolite were assessed (11,(45)(46)(47) . Although there was no formal interaction between level, source and infection on circulating levels of 25D 3 , at d10 pi when effects of infection were maximized, 25D 3 levels were similar between MD 3 and L25D 3 birds suggesting a better absorption efficiency for dietary 25D 3 (Figure 5a).…”
Section: Discussionsupporting
confidence: 89%
“…Overall, plasma 25D 3 levels were significantly increased by higher vitD supplementation and by offering 25D 3 as the source of vitD activity in both uninfected and infected birds. The interaction between level and source indicates that offering 25D 3 is more efficient than D3 in raising its concentration and is consistent with previous reports in chickens where serum or plasma concentrations of the metabolite were assessed (11,(45)(46)(47) . Although there was no formal interaction between level, source and infection on circulating levels of 25D 3 , at d10 pi when effects of infection were maximized, 25D 3 levels were similar between MD 3 and L25D 3 birds suggesting a better absorption efficiency for dietary 25D 3 (Figure 5a).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we focus on the skeletal muscle tissue of black Muscovy duck, because it is the prime part of carcass, and the yield of breast and leg meat is one of practical importance to the profitability of production [ 20 ]. Besides, muscle fiber numbers increase during embryonic development in poultry, after which myofiber numbers stop to increase, while myofiber volume still increases [ 8 ]. Therefore, we studied the gene expression patterns and network pathways at different developmental stages to further understand the molecular mechanism of duck skeletal muscle development.…”
Section: Discussionmentioning
confidence: 99%
“…During prenatal and very early postnatal development, muscle growth in vertebrates depends on an increasing number of muscle fibers (hyperplasia) [ 6 , 7 ]. After postnatal growth, the increase in skeletal muscle is mainly due to muscle hypertrophy, accompanied by the proliferation of satellite cells and then the new myonuclei is incorporated into existing myofibers [ 8 ]. Black Muscovy duck, an excellent meat duck breed in China, has the advantages of fast growth and high lean meat rate.…”
Section: Introductionmentioning
confidence: 99%
“…Bello et al (2014) reported that 25 (OH) D 3 dissolved in vaccine diluent buffer, did not negatively affect growth performance after hatching, while the hatching rate in the 25 (OH) D 3 -treated group was higher than in the control group, suggesting the possibility of improving hatching rates by administration of 25 (OH) D 3 . In addition, Hutton et al (2014) showed that dietary supplementation of 25 (OH) D 3 improved pectoral muscle development in broiler chicks.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, dietary administration of 25 (OH) D 3 improved the development of satellite cell activity, and growth of skeletal muscles (Hutton et al, 2014). However, the effects of Vit D 3 over 25 (OH) D 3 were not evaluated in embryonic nutrition.…”
Section: Introductionmentioning
confidence: 99%